Effectiveness of Post-Cooking Freezing and Lemongrass Fortification in Engineering Rice Starch Retrogradation to Reduce Glycemic Index and Starch Digestibility - Andi Laila Nugrawati Mustarim; Muhammad Iqbal Kusumabaka Rianse; Ilian Elvira; Fitria Dewi; Fatahu; Adri Aningsih Fardila Putri (Journal of Food and Agricultural Product, 2026)
Rice as the main staple food in Indonesia has a relatively high glycemic index, which may increase the risk of metabolic disorders. Rice engineering through the retrogradation process is one approach that can be applied to reduce its glycemic index. This study aimed to evaluate the effectiveness of post-cooking freezing in engineering rice starch retrogradation to promote resistant starch formation and reduce glycemic digestibility. Freezing was conducted stepwise for 24, 48, and 72 hours. Retrogradation was analyzed through amylose absorbance measurement, while digestibility was evaluated by in vitro starch hydrolysis with glucose determination using a colorimetric method based on 3,5-dinitrosalicylic acid (DNS). The results showed that post-cooking freezing was able to reduce starch digestibility through the formation of retrograded structures. The hydrolysis index of all samples ranged from 2.79 to 4.60%, and the predicted glycemic index was in the range of 41.24–42.25, which falls into the low category. The pattern of digestibility changes showed an increasing trend at 24 and 48 hours of freezing, followed by a decrease at 72 hours. This digestibility profile formed a U-shaped pattern, which may be attributed to the dynamic nature of the retrogradation process during freezing. Keywords: functional rice, resistant starch, predicted glycemic index, starch hydrolysis, in vitro